Optimalisasi Pembelajaran Kelistrikan di SMK melalui Penerapan Problem Based Learning untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa - Sucipto Aji Wibowo; Suyitno Suyitno; Arif Irawan; Aditya Alvin Fahriza; Indra Briyan Saputra (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study aims to improve the activeness and learning outcomes of students in the electrical system competency of class XI TSM 1 SMK Al Mu'allim Cilacap through the application of the Problem Based Learning (PBL) learning method. This study is a Classroom Action Research (CAR) with the Kurt Lewin model which is carried out in three cycles because it has achieved the success indicators of the action. The success indicators of this study are more than 75% of student activity and 75% of students achieving KKTP of 75. The subjects of this study were class XI TSM 1 SMK Al Mu'allim Cilacap students in the 2024/2025 Academic Year, totaling 27 students. Data collection techniques in this study used observation, learning outcome tests, and documentation. The results of the study show that through the application of the Problem Based Learning (PBL) learning method, it can improve the activeness and learning outcomes of students in the Motorcycle Electrical System Maintenance and Repair Elements. This can be seen from: (1) an increase in student learning activeness in each cycle. Learning engagement in cycle I was 61.1%, cycle II 66.7%, and cycle III 78.5%; (2) there was an increase in the class average and student learning achievement. The class average in cycle I was 67, cycle II 75, and cycle III 81. Meanwhile, student learning achievement in cycle I was 40.7%, cycle II 59.3%, and cycle III 77.8%. Therefore, it can be concluded that the problem-based learning method has an effect on increasing student engagement and learning outcomes in the Motorcycle Electrical System Maintenance and Repair Element for class XI TSM 1 of SMK Al Mu'allim Cilacap in the 2024/2025 academic year.